Sex-Specific Differences in Resolution of Airway Inflammation in Fat-1 Transgenic Mice Following Repetitive Agricultural Dust Exposure - Ulu, Arzu; Velazquez, Jalene V.; Burr, Abigail; Sveiven, Stefanie N.; Yang, Jun; Bravo, Carissa; Hammock, Bruce D.; Nordgren, Tara M. (Frontiers in Pharmacology, 2022)
In agriculture industries, workers are at increased risk for developing pulmonary diseases due to inhalation of agricultural dusts, particularly when working in enclosed confinement facilities. Agricultural dusts inhalation leads to unresolved airway inflammation that precedes the development and progression of lung disease. We have previously shown beneficial effects of the omega-3 polyunsaturated fatty acid (ω-3 PUFA) DHA in protecting against the negative inflammatory effects of repetitive dust exposure in the lung. Dietary manipulation of pulmonary disease risk is an attractive and timely approach given the contribution of an increased ω-6 to ω-3 PUFA ratio to low grade inflammation and chronic disease in the Western diet. To prevent any confounding factors that comes with dietary supplementation of ω-3 PUFA (different sources, purity, dose, and duration), we employed a Fat-1 transgenic mouse model that convert ω-6 PUFA to ω-3 PUFA, leading to a tissue ω-6 to ω-3 PUFA ratio of approximately 1:1. Building on our initial findings, we hypothesized that attaining elevated tissue levels of ω-3 PUFA would attenuate agricultural dust-induced lung inflammation and its resolution. To test this hypothesis, we compared wild-type (WT) and Fat-1 transgenic mice in their response to aqueous extracts of agricultural dust (DE). We also used a soluble epoxide hydrolase inhibitor (sEH) to potentiate the effects of ω-3 PUFA, since sEH inhibitors have been shown to stabilize the anti-inflammatory P450 metabolites derived from both ω-3 and ω-6 PUFA and promote generation of specialized pro-resolving lipid mediators from ω-3 PUFA. Over a 3-week period, mice were exposed to a total of 15 intranasal instillations of DE obtained from swine confinement buildings in the Midwest. We observed genotype and sex-specific differences between the WT vs. Fat-1 transgenic mice in response to repetitive dust exposure, where three-way ANOVA revealed significant main effects of treatment, genotype, and sex. Also, Fat-1 transgenic mice displayed reduced lymphoid aggregates in the lung following DE exposure as compared to WT animals exposed to DE, suggesting improved resilience to the DE-induced inflammatory effects. Overall, our data implicate a protective role of ω-3 FA in the lung following repetitive dust exposure.